Income Analysis Of Layer Business In Barabali Village Batukliang Sub-District Central Lombok - Purwadi Purwadi; Ria Harmayani; Yuni Mariani; Ni Made Andry Kartika (Baselang, 2022)
Laying hens are one of the poultry commodities that have an important role as egg producers in supporting the availability of cheap and easy to obtain animal protein. Provincial government NTB has determined that one of six strategic programs in the vision and mission of the 2019-2023 Regional Medium Term Development Plan (RPJMD) is animal husbandry and processing industries (DisKop NTB, 2022), including laying hens. This study aims to determine the amount of business income and the efficiency of the laying hen farming business which was carried out in Barabali Village, Batukliang District, Central Lombok Regency from August to October 2022. The method used in this research is a survey method and interviews with laying hen breeders who have chicken farms with a capacity of 500-1,000 heads. The types of data used are primary data and secondary data. The data analysis used is business income analysis by using the formula: π = TR – TC or income (π) is obtained from the difference in total revenue/acceptance (TR) and total cost/variable costs, while business efficiency is calculated using the formula RC Ratio = PK (Gross Income) divided by TBP (Total Cost of Production). The results showed that the average income of laying hens in Barabali Village was Rp. 380,080,000,-. The efficiency level of laying hen farming business based on the R/C ratio is 2.29, meaning that this business is feasible to develop. Laying chicken farms in rural areas should increase production by increasing capacity because they still have vacant land and utilize chicken manure waste and used feed sacks as additional income to increase business revenue.